PRESERVING ACEH CULTURE THROUGH RANUP MAKING TRAINING: A LOCAL WISDOM-BASED COMMUNITY SERVICE PROGRAM FOR TEENAGE GIRLS - Fanny Nailufar; Noviami Trisniarti; Cut Putri Mellita Sari; Khairisma; Fadhilah; Rani Puspita Ningrum (RADJA PUBLIKA, 2024)
The tradition of ranup seulaseh, or ornamental betel, is one of Aceh's cultural heritage that has a deep philosophical meaning as a symbol of honor, togetherness, and love. However, modernization has led to a cultural shift that threatens its sustainability, especially in urban areas. This article discusses community service activities through training to weave ranup seulaseh in Gampong Blang Pulo, Lhokseumawe, which aims to preserve Acehnese culture while empowering women as the main actors of this tradition. The activity method includes interactive discussions, demonstrations, and practices for making ranup seulaseh. The results showed increased participants' understanding of Acehnese cultural values and the skill of assembling ranup seulaseh as a business opportunity. The participants' enthusiasm showed the potential for preserving this tradition to continue to be inherited. This training supports cultural preservation and contributes to women's economic empowerment. Recommendations were given for implementing further training and developing marketing strategies for local cultural products.